2023
DOI: 10.1111/cbdd.14287
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid inhibits the formation of hypertrophic scars by suppressing TGF‐β/Smad signaling pathway activity

Abstract: Hypertrophic scar (HS) is a benign fibroproliferative skin disease, which lacks the ideal treatment and drugs. Ellagic acid (EA) is a natural polyphenol that prevents fibroblasts from proliferating and migrating. This study aimed to determine the role of EA in HS formation and its possible mechanism by in vitro experiments. HS fibroblasts (HSFs) and normal fibroblasts (NFs) were separated from HS tissue and normal skin tissue, respectively. HSFs were treated with 10 and 50 μM EA to assess their effect on HS fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
1
0
2
Order By: Relevance
“…A study conducted by Zhao and colleagues [ 63 ] in vitro using fibroblasts demonstrated that EA significantly reduced the expression of TGF-β1 and phosphorylation of Smad2 and Smad3, thereby preventing the activation of the canonical TGF-β/Smad2/3 signaling pathway. In addition, EA treatment decreased the viability and migration of fibroblasts and downregulated the expression of ECM components including collagen type I and fibronectin.…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%
“…A study conducted by Zhao and colleagues [ 63 ] in vitro using fibroblasts demonstrated that EA significantly reduced the expression of TGF-β1 and phosphorylation of Smad2 and Smad3, thereby preventing the activation of the canonical TGF-β/Smad2/3 signaling pathway. In addition, EA treatment decreased the viability and migration of fibroblasts and downregulated the expression of ECM components including collagen type I and fibronectin.…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%
“…Gıda örneklerinde, çevre örneklerinde, insan kanında ve serumunda, plasentada, idrarda ve anne sütünde ve hatta kozmetik ürünlerde BPA tespit edilmiştir (37,38). Bir polifenol olan EA, ağırlıklı olarak meyvelerde, sebzelerde ve bazı bitkisel gıdalarda bulunan (22) farklı türdeki kronik hastalıklara karşı potansiyel biyoaktiviteye sahiptir (23). EA'nın oksidatif strese karşı belirgin zayıflatıcı etki yarattığı ve enflamasyona karşı önemli önleyici rol oynadığı ve organ toksisitesine ilişkin yüksek biyokimyasal belirteçlere (ör: kreatinin) karşı dikkate değer koruma sağladığı bildirilmiştir (24).…”
Section: İstatistiksel Bulgularunclassified
“…Bir polifenol olan EA (Ellajik asit), ağırlıklı olarak meyvelerde, sebzelerde ve bazı bitkisel gıdalarda bulunan (22) farklı türdeki kronik hastalıklara karşı potansiyel biyoaktivite özelliği taşıyan bir bileşendir (23). EA'nın oksidatif strese karşı belirgin zayıflatıcı etki yarattığı ve enflamasyona karşı önemli önleyici rol oynadığı ve organ toksisitesine ilişkin Med J West Black Sea 2024;8(1): 58-66 yüksek biyokimyasal belirteçlere karşı dikkate değer koruma sağladığı bildirilmiştir (24).…”
Section: Introductionunclassified